IKEA’s Corporate Social Responsibility - Abdulaziz Al Shuwaler; Majdi Anwar Quttainah; Daisy Mui Hung Kee; Choo Mun Kei; Er Jia Qi; Ewe Cai Wen; Gao Qu; Muskan Saxena; Rudresh Pandey (AIBPM Publisher, 2020)
Corporate Social Responsibility (CSR) is an evolving business practice that helps the company to be socially accountable. It appears to play an important role in enhancing the economic, social, and environmental performances. IKEA is an internationally known home furnishing retailer that has grown rapidly since the year 1943. IKEA maintains a sustainable business by implementing CSR as a global supply chain. The purpose of this research is to analyze CSR practices in global supply chains. Our investigation will examine how CSR brings benefits to the three indicators while the organization boosts its brands. The results of the study indicate that CSR practices bring a positive impact on the organization.